Método deductivo para el inicio de la temática: fenómenos y naturaleza de la luz a partir del fenómeno de difracción - Galindo, Angela Marcela; Murcia, Deicy Paola; Morales, Johana Katerine (Góndola, enseñanza y aprendizaje de las ciencias, 2008)
In this work we develop a didactic material on the topic of diffraction of light as we consider that this is a starting point for study different wave phenomena. The didactic proposal consisted in the elaboration of a brochure to introduce students and to capture his attention towards analysis of this phenomenon, after that, laboratory experience was developed, orienting the student to confront his argumentations before and after observing the phenomenon. Results obtained showed that the fact of mentally posing the situation and seeking explanation in the common logic and then confronting with real experience generates a mental impact that contributes to knowledge construction, not as the search for some truth, but as the search from logical and scientific explanations to what is observed in the natural world.